نمذجة جزيئية لدراسة الخصائص الفيزيوكيميائية لمركبات حلقية غير متجانسة ذات فعالية بيولوجية - دركي نور الهدى (Universty Of El-oued جامعة الوادي, 2025)
الملخص: يعد مرض السكري من النوع الثاني أحد أكثر الأمراض المزمنة انتشارا على مستوى العالم، وأثبتت العديد من الدراسات فعالية مشتقات )TDZ( Thiazolidine-2,4-dioneفي تثبيط البروتين PTP1Bالذي يعتبر منظم سلبي لمسار إشارات الأنسولين، حيث يقوم بإزالة مجموعة الفوسفات من مستقبلات الأنسولين والركائز المرتبطة بها، مما يقلل من نشاط مسار الإشارة وبالتالي يضعف استجابة الخلايا للأنسولين . وعليه فإن تثبيط PTP1Bقد يساعد في تعزيز حساسية الإنسولين عن طريق الحفاظ على نشاط مسار إشارات الإنسولين لفترة أطول. تهدف هذه الأطروحة إلى تصميم وتطوير مشتقات جديدة من مركبات )TDZ( Thiazolidine-2,4-dioneبخصائص دوائية واعدة لعلاج داء السكري من النوع الثاني، وذلك بالاعتماد على تقنيات تصميم الأدوية بمساعدة الحاسوب (.)CADDفي البداية، قمنا في هذه الدراسة بتحليل العلاقة الكمية بين البنية والفعالية البيولوجية ) (QSARلـ 27مشتقا من 5-(substituted ،benzylidene) Thiazolidine-2,4-dioneباستخدام التحليل الإحصائي الخطي المتعدد) . (MLRللتحقق من دقة النموذج وموثوقيته، تم تطبيق طريقة ) ،(LOOإلى جانب معاملات إحصائية متقدمة، واختبار Yالعشوائي، وتحديد مجال قابلية التطبيق، مما أكد كفاءة النموذج في التنبؤ بالنشاط البيولوجي للمركبات الجديدة ضمن هذه السلسلة.في الخطوة التالية، تم تصميم سبعة مشتقات جديدة من مركبات 5-(substituted benzylidene) Thiazolidine-2,4-dioneمع التنبؤ بقيم pIC50لها اعتماد ا على نموذج QSARالمطور، وباستخدام المركب ) 7e(refكقالب مرجعي، حيث أظهرت دراسة الالتحام الجزيئي المضاد للبروتين PTP1Bان المركبات المصممة تمتلك طاقات ارتباط حرة أفضل مقارنة بالمركب المرجعي ).7e(refو قد تم تقييم المركبات المصممة من خلال دراسات الخصائص الدوائية و ،ADMETحيث تبين توافقها مع المعايير المعتمدة للاستخدام البشري دون تسجيل آثار جانبية. كما تم توقع النشاط البيولوجي المحتمل لهذه المركبات عبر أداة . PASSعلاوة على ذلك، تم إجراء تحليل DFTلتقييم ثباتها البنيوي وفاعليتها الكيميائية، وأكدت محاكاة الديناميكا الجزيئية للمركب 11cاستقراره في بيئة مشابهة للظروف البيولوجية. Abstract: Type 2 diabetes is one of the most prevalent chronic diseases worldwide. Many studies have proven the effectiveness of Thiazolidine-2,4-dione (TDZ) derivatives in inhibiting PTP1B protein, which is a negative regulator of the insulin signaling pathway. PTP1B removes phosphate groups from insulin receptors and their associated substrates, reducing the activity of the signaling pathway and thereby impairing the cellular response to insulin. Therefore, PTP1B inhibition may help enhance insulin sensitivity by maintaining insulin signaling activity for a longer period. This thesis aims to design and develop new derivatives of Thiazolidine-2,4-dione (TDZ) compounds with promising pharmacological properties for the treatment of type 2 diabetes, relying on computer-aided drug design (CADD) techniques.]2[ Initially, this study performed a quantitative structure-activity relationship (QSAR) analysis of 27 derivatives of 5-(substituted benzylidene) Thiazolidine-2,4-dione using multiple linear regression (MLR) statistical analysis. To verify the accuracy and reliability of the model, the leave-one-out (LOO) method was applied, along with advanced statistical metrics, random Ytest, and applicability domain determination, confirming the model's efficiency in predicting the biological activity of new compounds in this series. In the next step, seven new derivatives of 5-(substituted benzylidene) Thiazolidine-2,4-dione were designed, with predicted pIC50 values based on the developed QSAR model, using compound 7e(ref) as a reference template. Molecular docking studies against the PTP1B protein showed that the designed compounds exhibited better free binding energies compared to the reference compound 7e(ref). The designed compounds were evaluated through pharmacokinetic and ADMET studies, demonstrating their compliance with established criteria for human use without adverse side effects. Potential biological activity was predicted using the PASS tool. Additionally, a DFT analysis was performed to assess their structural stability and chemical efficacy, and molecular dynamics simulations of compound 11c confirmed its stability in a biological-like environment.
أطروحةدكتوراه تخصص كيمياء تحليلية في العلوم الدقيقة
Keywords: مرض السكري من النوع الثاني ، 5-(substituted benzylidene) Thiazolidine-2; 4-dione ، بروتين PTP1B ، نموذج QSAR ، الالتحام الجزيئي ، ADMET ، PASS ، DFT ، الديناميكا الجزيئية; Type 2 diabetes; 5-(Substituted Benzylidene) Thiazolidine-2; 4-dione; PTP1B protein; QSAR Model; Molecular Docking; ADMET; PASS; DFT; Molecular Dynamics